Implementation of Differentiated Instruction for BIPA Students in Learning the Indonesian Language - Heny Subandiyah; Fahri Fahri; Fithriyah Inda Nur Abida; Nadia Cao Jia; Abdul Rosyid; Etik Minarti (Journal Evaluation in Education (JEE), 2026)
Purpose of the Study: This study explores the implementation of differentiated instruction in teaching Bahasa Indonesia to foreign speakers, focusing on how adaptive teaching strategies address linguistic and cultural barriers while enhancing learners' communicative competence. Differentiated instruction allows educators to modify content, processes, and assessments based on students’ varying proficiency levels, learning preferences, and cultural contexts creating an inclusive and engaging language-learning environment. Methodology: A qualitative case study approach was employed to provide an in-depth understanding of instructional practices. The participants were 20 foreign students (8 males and 12 females) from diverse countries enrolled in a Bahasa Indonesia course at the State University of Surabaya. Data were gathered through classroom observations, semi-structured interviews, and document analysis. Thematic analysis was applied to identify patterns in instructional adaptation, learner engagement, and classroom implementation challenges. Main Findings: The results demonstrated that differentiated instruction significantly improved students’ language acquisition, participation, and motivation. Learners benefited from varied learning activities, technology-enhanced tools, and flexible assessment approaches that accommodated different linguistic abilities and cultural backgrounds. Nevertheless, the study identified challenges in lesson preparation time and teachers’ capacity to maintain instructional consistency. Novelty/Originality of this Study: This research offers one of the first comprehensive examinations of differentiated instruction in the context of Bahasa Indonesia as a foreign language. It offers a culturally responsive pedagogical model that bridges linguistic diversity with inclusive education principles, providing theoretical and practical guidance for educators seeking to enhance equitable, learner-centered language teaching practices in multicultural classrooms.